Application of decellularized tissue for soft-hard interregional regeneration - Suzuki, Mika; Kimura, Tsuyoshi; Hashimoto, Yoshihide; Kishida, Akio (Frontiers in Bioengineering and Biotechnology, 2025)
Decellularized tissue refers to extracellular matrix (ECM) derived from living tissue by removing the cellular components and is used for tissue regeneration. Various decellularized tissue sheets and powders, such as the dermis, urinary bladder matrix, and small intestinal submucosa, have been clinically used as covering and prosthetic materials. Moreover, there is growing interest in the use of decellularized tissue for soft-hard interregional tissue regeneration, including in the ligament-bone, tendon-bone, and periodontal ligament-bone interfaces. The focus in these applications lies in the mechanical properties of the decellularized tissue. Decellularized ligaments and tendons have been developed using various decellularization methods, with a focus on maintaining their shape and mechanical properties, and have been applied orthotopically or ectopically to ligaments and tendons. In the ligament-bone interface, it is suggested that decellularized ligament and tendon are regenerated through the migration and rearrangement of host cells, which is referred to as “in situ tissue regeneration.” It is also proposed that decellularized tissue can be used to prepare the complex structure of soft-hard interregional tissue, which consists of an ECM and cell populations with gradual change. In this case, the decellularized soft tissues of ligaments, tendons, pericardium, and others are fabricated and modified with hard tissue components to mimic the gradual structure of soft-hard interregional tissue. In this review, we present a detailed discussion of the regeneration of soft-hard interregional tissue using decellularized tissue.